A qualitative study of symptoms and psychological experience of patients with delayed resolution after microvascular decompression for hemifacial spasm (面肌痉挛行微血管减压术后延迟治愈患者症状体验和心理感受的质性研究) - JING Dan (井丹); LYU Yan (吕燕); XU Zai (徐再) (中西医结合护理)
Objective　Methods A purposive sampling strategy was used to choose patients with delayed resolution after microvascular decompression for hemifacial spasm. The qualitative phenomenological study was conducted and two trained research nurses used semi-structured interview on 10 patients. Each interview was recorded on audiotape and later transcribed verbatim , and was stopped when the information reached a saturated level. The Colaizzi s 7-step analysis method was used to analyze the recording materials. Results There are four main themes: Treatment of disease and cognition; Psychological issues such as excessive negative expectation, expectation bias, autosuggestion of surgery failure and positive coping style; Physical issuers such as headache, nausea and vomiting dizziness; incomprehension and support of social relations. Conclusion Patients with delayed resolution after microvascular decompression for hemifacial spasm suffered physical, mental and social stress. Medical staff should take a comprehensive dynamic evaluation on disease awareness, physical issues, psychological issues and social support system, try to understand the symptoms and psychological experience of patients, and provide professional guidance and individualized nursing intervention, in order to relieve discomfort, improve the mental health, and improve the satisfaction and therapeutic experience of patients. To investigate the　symptoms and psychological experience of patients with delayed resolution after microvascular decompression for hemifacial spasm, in order to improve the medical staff awareness of patients ‘symptoms and psychological experience after surgery, and provide reference for improving nursing procedures of symptoms management and psychological care. (目的 本研究旨在探讨面肌痉挛行微血管减压术后延迟治愈患者真实的症状体验和心理感受, 以期为医护人员全面掌握患者术后的症状表现及心理状态, 并为完善术后护理程序症状管理及心理护理干预提供依据。方法 采用目的抽样法, 选取符合要求的江苏省南京市某三甲医院神经外科 2021 年 1 月—5 月面肌痉挛行微血管减压术后延迟治愈患者, 采用现象学研究方法, 由 2 名接受过访谈技巧培训的护士采用质性研究方法进行半结构访谈。现场进行笔录和录音, 信息饱和时终止访谈, 本研究共纳入10例面肌痉挛行微血管减压术后延迟治愈患者, 并运用Colaizzi7 步分析法分析访谈资料。结果 访谈内容最终归纳为 4 个主题, 疾病的治疗与认知方面; 心理方面: 过度负性预期、与心理预期的偏差、自我暗示手术失败、积极面对; 生理方面: 头痛、恶心呕吐、头晕; 社会支持系统: 社会关系的不理解、社会关系的支持。结论 面肌痉挛行微血管减压术后延迟治愈的患者承受着生理、心理、社会支持系统多方面压力, 医护人员应对患者的疾病认知水平、生理方面、心理方面、社会支持系统进行全面动态评估, 了解患者最真实的症状体验和心理感受, 给予专业的指导和个性化护理干预, 减轻患者术后不适症状, 促进心理健康, 提高患者满意度, 改善患者治疗体验。)